Traumatic Brain Injury Exposure Lowers Age of Cognitive Decline in AD and Non-AD Conditions - Iacono, Diego; Raiciulescu, Sorana; Olsen, Cara; Perl, Daniel P. (Frontiers in Neurology, 2021)
We aimed to detect the possible accelerating role of previous traumatic brain injury (TBI) exposures on the onset of later cognitive decline assessed across different brain diseases. We analyzed data from the National Alzheimer’s Coordinating Center (NACC), which provide information on history of TBI and longitudinal data on cognitive and non-cognitive domains for each available subject. At the time of this investigation, a total of 609 NACC subjects resulted to have a documented history of TBI. We compared subjects with and without a history of previous TBI (of any type) at the time of their first cognitive decline assessment, and termed them, respectively, TBI+ and TBI- subjects. 361 TBI+ subjects (229 male/132 female) and 248 TBI- subjects (156 male/92 female) were available. The analyses included TBI+ and TBI- subjects with a clinical diagnosis of Mild Cognitive Impairment, Alzheimer’s disease, Dementia with Lewy bodies, Progressive supranuclear palsy, Corticobasal degeneration, Frontotemporal dementia, Vascular dementia, non-AD Impairment, and Parkinson’s disease. The data showed that the mean age of TBI+ subjects was lower than TBI- subjects at the time of their first cognitive decline assessment (71.6±11.2 vs. 74.8±9.5 year; p<0.001). Moreover, the earlier onset of cognitive decline in TBI+ vs. TBI- subjects was independent of sex, race, attained education, APOE genotype, and importantly, clinical diagnoses. As for specific cognitive aspects, MMSE, Trail Making Test part B and WAIS-R scores did not differ between TBI+ and TBI- subjects, whereas Trail Making Test part A (p=0.013) and Boston Naming test (p=0.008) did. In addition, data showed that neuropsychiatric symptoms (based on Neuropsychiatry Inventory [NPI]) were much more frequent in TBI+ vs. TBI- subjects, including AD and non-AD neurodegenerative conditions such as PD. These cross-sectional analyses outcomes from longitudinally-assessed cohorts of TBI+ subjects that is, subjects with TBI exposure before the onset of cognitive decline in the contest of different neurodegenerative disorders and associated pathogenetic mechanisms, are novel, and indicate that a previous TBI exposure may act as a significant “age-lowering” factor on the onset of cognitive decline in either AD and non-AD conditions independently of demographic factors, education, APOE genotype, and current or upcoming clinical conditions.